Search for a new resonance decaying to a W or Z boson and a Higgs boson in the ℓℓ/ℓν/νν+bb[bar] final states with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Hanke, Paul; Jongmanns, Jan; Kluge, Eike-Erik; Kugel, Andreas; et al. (The European physical journal. C, Particles and fields, 2015)
A search for a new resonance decaying to a W or Z boson and a Higgs boson in the ℓℓ/ℓν/νν+bb¯ final states is performed using 20.3 fb−1 of pp collision data recorded at s√= 8 TeV with the ATLAS detector at the Large Hadron Collider. The search is conducted by examining the WH / ZH invariant mass distribution for a localized excess. No significant deviation from the Standard Model background prediction is observed. The results are interpreted in terms of constraints on the Minimal Walking Technicolor model and on a simplified approach based on a phenomenological Lagrangian of Heavy Vector Triplets.
*ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A. Baas, O. Brandt, J.I. Djuvsland, M. Dunford, M. Geisler, P. Hanke, J. Jongmanns, E.-E. Kluge, A. Kugel, V. Lang, K. Meier, S. Schaetzel, V. Scharf, S. Schmitt, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, M. Wessels [und 2805 weitere Personen]
Im Titel steht der zweite Buchstabe b mit einem Oberstrich
Gesehen am 09.07.2021